TP53 Mutation Status Influences Iron Regulatory Protein RNA Binding Activity and Sensitivity to Ferroptotic Cell Death. (29th May 2020) - Thompson, Laurie; Oliveira, Thais; Hermann, Evan; Montgomery, Mckale; Chowanadisai, Winyoo; Clarke, Stephen
Abstract: Objectives: The tumor suppressor gene TP53 is the most commonly mutated gene in human cancer, but mutations in TP53 do not just result in loss of tumor suppressor function, they can also promote cancer progression by altering cellular iron acquisition and metabolism. A newly identified role for TP53 in the mediation of iron homeostasis and cancer cell survival lies in the ability for TP53 to protect against ferroptosis, a form of iron mediated cell death. The purpose of this study was to determine the extent to which TP53 mutation status effects iron-mediated cell death in response to ferroptosis induction. We also measured TP53 dependent differences in iron regulatory protein (IRP) RNA binding activity to begin to clarify the mechanisms by which TP53 mutation status may influence sensitivity to ferroptosis. Methods: Using H1299 cells, which are null for TP53, we generated cell lines expressing either a tetracycline inducible wild-type TP53 gene, or a representative mutated TP53 gene from exemplary "hotspot" mutations in the DNA binding domain (R248, R273, R282, G245, R249 and R175). These six mutation types were selected because they represent 25% of all TP53 mutations in human cancer. To determine the influence of TP53 mutation status on sensitivity to ferroptotic cell death, we treated cells with erastin, a potent inducer of ferroptosis and measured differences in cell viability between these cell lines using PrestoBlue cell viability reagent. To assess mutant TP53-depenent differences in IRP RNA binding activity during ferroptosis we measured differences in IRP RNA binding activity via Electrophoretic Mobility-Shift Assay. Results: We found that TP53 mutants (R273, R248, R175, G245, and R249) were significantly less viable ( P < 0.05) after initiation of ferroptosis compared to cells expressing WT TP53. Following ferroptosis induction, we observed a significant ( P < 0.05) increase in IRP RNA binding in G245, R248, and R175 mutants. Conclusions: Our preliminary analyses indicate that TP53 mutants may be more sensitive to ferroptosis, but IRPs do not seem to be solely responsible for the increase in iron during ferroptotic cell death. Furthermore, ferroptosis may be a potential therapeutic target for cancers with these TP53 mutations but further investigation is warranted. Funding Sources: Internal funding at Oklahoma State University.